The interbank market puzzle - Franklin Allen; Giovanni Covi; Xian Gu; Oskar Kowalewski; Mattia Montagna (European Central Bank (ECB), 2020)
This study documents significant differences in the interbank market lending and borrowing levels across countries. We argue that the existing differences in interbank market usage can be explained by the trust of the market participants in the stability of the country's banking sector and counterparties, proxied by the history of banking crises and failures. Specifically, banks originating from a country that has lower level of trust tend to have lower interbank borrowing. Using a proprietary dataset on bilateral exposures, we investigate the Euro Area interbank network and find the effect of trust relies on the network structure of interbank markets. Core banks acting as interbank intermediaries in the network are more significantly influenced by trust in obtaining interbank funding, while being more exposed in a community can mitigate the negative effect of low trust. Country-level institutional factors might partially substitute for the limited trust and enhance interbank activity.
Keywords: G01; G21; G28; D85; 330; Interbank market; Trust; Networks; Centrality; Community detection